An evaluation of congenital talipes equinovarus patients treated by various methods - Goel, Navneet; Goyal, Ashish; Sharma, Mohit (International Journal of Research in Orthopaedics, 2020)
Background: Idiopathic congenital talipes equinovarus is one of the commonest congenital anomaly. Although treatment provides many options, near universal agreement exists that initial management should consist of gentle manipulation of the affected foot. In developing country like India presentation is extremely variable from soon after birth to very late childhood and irregular follow up makes treatment more difficult. Methods: 100 cases of congenital talipes equinovarus who attended the Orthopedics OPD of our hospital (March 2013 to 2016) were taken up. In neonates with delicate skin, the passive manipulation was demonstrated to the mother which they did 5-6 times daily. The application of plaster of Paris cast and passive manipulation was done every 15th day upto 3 months of age. After the 3-month age, passive manipulation was done every 3 weeks. If no normalization, surgery was advised and done to correct the resistant component accordingly. All the analyses were performed in R-programming language (R- 3.0.0). Results: 6 cases,10 feet were lost during follow-up. Results were assessed in 134 feet, 128 cases managed conservatively, 13 surgically. Results were assessed according to clinical, radiological criteria of Beatson and Pearson. 13 feet were operated of 144 feet,11 cases posteromedial soft tissue release (PMSTR) was done. In two Joshi’s external stabilizing system (JESS) fixator was applied. Conclusions: Majority of cases can be treated successfully by conservative means and only in 11 cases PMSTR was done, 2 cases of relapsed feet JESS was applied.